Outflows of Capital from China - Wall, David (OECD Development Centre Working Papers, 1997)
While the world has been mesmerised by China's emergence as a major player in international trade, now being one of the world's top ten traders, and also as an absorber of international capital (second only to the United States), China's state-owned and other public sector enterprises have been quietly growing in importance as a source of international capital. Chinese enterprises now have foreign direct investment in virtually every country in the world and across the whole spectrum of economic activities, from merchant banking to fish processing and forestry. This paper reviews the available aggregate data on outflows of capital from China. It also examines such data as is available on individual foreign direct investments. One conclusion which emerges is that while such outflows are growing and being disbursed on a global basis there is a significant concentration in a small number countries, in particular Australia, Canada and the United States, in addition to the strong ...